CX3CR1 differentiates F4/80low monocytes into pro-inflammatory F4/80high macrophages in the liver. Issue 1 (December 2018) - Lee, Young-Sun; Kim, Myung-Ho; Yi, Hyon-Seung; Kim, So; Kim, Hee-Hoon; Kim, Ji; Yeon, Jong; Byun, Kwan; Byun, Jin-Seok; Jeong, Won-Il
Abstract The expression of chemokine receptor CX3 CR1 is related to migration and signaling in cells of the monocyte-macrophage lineage. The precise roles of CX3 CR1 in the liver have been investigated but not clearly elucidated. Here, we investigated the roles of CX3 CR1 in hepatic macrophages and liver injury. Hepatic and splenic CX3 CR1low F4/80low monocytes and CX3 CR1low CD16− monocytes were differentiated into CX3 CR1high F4/80high or CX3 CR1high CD16+ macrophages by co-culture with endothelial cells. Moreover, CX3 CL1 deficiency in human umbilical vein endothelial cells (HUVECs) attenuated the expression of interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α), whereas recombinant CX3 CL1 treatment reversed this expression in co-cultured monocytes. Upon treatment with clodronate liposome, hepatic F4/80high macrophages were successfully depleted at day 2 and recovered similarly in CX3 CR1+/GFP and CX3 CR1GFP/GFP mice at week 4, suggesting a CX3 CR1-independent replacement. However, F4/80high macrophages of CX3 CR1+/GFP showed a stronger pro-inflammatory phenotype than CX3 CR1GFP/GFP mice. In clodronate-treated chimeric CX3 CR1+/GFP and CX3 CR1GFP/GFP mice, CX3 CR1+ F4/80high macrophages showed higher expression of IL-1β and TNF-α than CX3 CR1− F4/80high macrophages. In alcoholic liver injury, despite the similar frequency of hepatic F4/80high macrophages, CX3 CR1GFP/GFP mice showed reduced liver injury, hepatic fat accumulation, and inflammatory responses than CX3 CR1+/GFP mice. Thus, CX3 CR1 could be a novel therapeutic target for pro-inflammatory macrophage-mediated liver injury.